Remarques sur le rôle de l’intonation dans le traitement de l’information - Gilles Col (Corela)
The present article starts from the following question: which instruction of meaning construction is given by intonation? Intonation seemingly gives an instruction aiming at structuring or restructuring the verbal scene (the representation yielded by the sentence). Its action does not concern the processing of the units of the sentence; it rather favours attentional focalisation. What is salient in the sentence is neither some particular units, not their schematic forms, but various steps of the coalescence of schematic forms, various « moments » of the construction of meaning. Besides, the prosodic instruction seems to be given by some units acting as « check points » in the coalescence of schematic forms and being profiled as concentration points in the structuring of the verbal scene, thus drawing specific regions on the scene.